2013
DOI: 10.1167/iovs.12-10537
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Hemorrhage Causes Retinal Vascular Dysfunction via Plasma Kallikrein

Abstract: PURPOSE. Retinal hemorrhages occur in a variety of sightthreatening conditions including ocular trauma, high altitude retinopathy, and chronic diseases such as diabetic and hypertensive retinopathies. The goal of this study is to investigate the effects of blood in the vitreous on retinal vascular function in rats.METHODS. Intravitreal injections of autologous blood, plasma kallikrein (PK), bradykinin, and collagenase were performed in Sprague-Dawley and Long-Evans rats. Retinal vascular permeability was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…49,50 We have previously shown that PKal induces proteolysis of basement membrane and extracellular matrix proteins including multiple collagen isoforms, laminin b1 and g1, nidogen 1 and 2, and fibronectin in brain astrocyte and pericytes. 26,51 Moreover, PKal can interfere with collageninduced platelet activation leading to intracerebral hematoma expansion in rodent models. 11 These reports have revealed that PKal has collagen-binding and collagenase-like activities that might facilitate hemorrhage under certain pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49,50 We have previously shown that PKal induces proteolysis of basement membrane and extracellular matrix proteins including multiple collagen isoforms, laminin b1 and g1, nidogen 1 and 2, and fibronectin in brain astrocyte and pericytes. 26,51 Moreover, PKal can interfere with collageninduced platelet activation leading to intracerebral hematoma expansion in rodent models. 11 These reports have revealed that PKal has collagen-binding and collagenase-like activities that might facilitate hemorrhage under certain pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…tPA induced concentration-dependent increases in kallikrein-like activity (P , .01 vs vehicle; Figure 1A). The contribution of PKal to tPAstimulated kallikrein activity was demonstrated using a selective PKal inhibitor BPCCB 25,26 ( Figure 1A, insert) and PPK-deficient plasma ( Figure 1B), which decreased substrate hydrolysis by 83% and 74%, respectively. To investigate the factors that may contribute to tPA-mediated PKal activity, we incubated tPA (360 nM) with normal human plasma and with plasma-depleted in plasminogen or FXII.…”
Section: Tpa-mediated Pkal Activation Via Plasmin and Fxii In Human Pmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that intraocular hemorrhage causes retinal vascular dysfunction via the action of plasma kallikrein (Liu et al, 2013). These data indicate that the effects of plasma-or tissue-derived kallikrein are different.…”
Section: Diabetic Retinopathy and Kallikreinmentioning
confidence: 83%
“…Moreover, the contribution of the kininkallikrein system to developing CNV was limited (Nagai et al, 2007). However, the plasma kallikrein correlates with intraocular hemorrhage and prokallikrein increases the retinal thickness (Clermont et al, 2011;Liu et al, 2013). These reports suggest that plasma kallikrein and prokallikrein may cause partial aggravation of AMD.…”
Section: Age-related Macular Degeneration and Kallikreinmentioning
confidence: 99%